Impact of wideband wavelength conversion on the performance of optical networks - Fagotto, Eric A.M.; Bonani, Luiz H.; Rossi, Sandro M.; Marconi, Jorge D.; Abbade, Marcelo L.F. [UNESP]; Aldaya, Ivan [UNESP]; Miranda, Uriel R.C.; Belançon, Marcos P. (Elsevier, 2024)
In this paper, it is proposed and numerically tested a 4 −THz guard-band-less integrated all-optical wavelength converter (iAOWC) with two four-wave mixing (FWM) stages. The nonlinear media used in each stage is a waveguide with a tellurite core that is buried into a SiO2 substrate. The core is shaped as two interleaved spirals connected in their centers by two arcs of a circle to minimize bend loss. The iAOWC can continuously shift a 4 −THz WDM bandwidth from the C- to the L-band and vice versa. In the physical layer simulations, 80×28−GBaud, as DP-QPSK and DP-16QAM, 50-GHz-WDM signals were propagated, respectively, through typical distances found in ultra-long-haul and long-haul transmission systems. For up to four wavelength conversions, the penalties imposed on the signals bit-error-ratios by the iAOWCs were negligible. In the network layer simulations, blocking probabilities were estimated in the CORONET and PANEUR topologies supposing an incremental traffic scenario. Physical layer results were fundamental for the parameters (route lengths, wideband conversion, and spectral shift) considered in the network layer analysis. All network links could carry up to 160 wavelengths that extended from C- to L-band. It is shown that by using an iAOWC with bandwidth of 4-THz instead of 1-THz, both with the same spectral shift capability, to match the blocking probabilities achieved with OEOWCs, this would lead to a reduction of 50% and 40% in the number of required devices for the CORONET and PANEUR topologies, respectively. Finally, this is the first time that it is reported a joint analysis of the physical and network layers regarding the impact of wideband wavelength conversion on the performance of optical networks, specially using an integrated all-optical device and under real-world traffic scenarios.